The Metaverse as a Virtual Form of Data-Driven Smart Urbanism: On Post-Pandemic Governance through the Prism of the Logic of Surveillance Capitalism - Bibri, Simon Elias; Allam, Zaheer (Smart cities (Basel), 2022)
The Metaverse, as a gigantic ecosystem application enabled mainly by Artificial Intelligence (AI), the IoT, Big Data, and Extended Reality (XR) technologies, represents an idea of a hypothetical "parallel virtual environment" that incarnates ways of living in virtually inhabitable cities. It is increasingly seen as a transition from smart cities to virtual cities and a new target for city governments to attain “new” goals. However, the Metaverse project was launched amid the COVID-19 pandemic, a crisis purported to be a rare opportunity that should be seized to reset and reimagine the world—though mainly in regard to its digital incarnation, and what this entails in terms of both cementing and normalizing the corporate-led, top-down, technocratic, tech-mediated, algorithmic mode of governance, as well as new forms of controlling ways of living in urban society. The “new normal” has already set the stage for undemocratically resetting and unilaterally reimagining the world, resulting in an abrupt large-scale digital transformation of urban society, a process of digitization and digitalization that is in turn paving the way for a new era of merging virtuality and urbanity. This has raised serious concerns over the risks and impacts of the surveillance technologies that have been rapidly and massively deployed in the wake of the COVID-19 pandemic. These concerns also relate to the global architecture of the computer mediation of the Metaverse upon which the logic of surveillance capitalism depends, and which is constituted by control and commodification mechanisms that seek to monitor, predict, control, and trade the behavior of human users, as well as to exile them from their own. This viewpoint paper explores and questions the Metaverse from the prism of the social and economic logic of surveillance capitalism, focusing on how and why the practices of the post-pandemic governance of urban society are bound to be undemocratic and unethical. The novelty of the viewpoint lies in providing new insights into understanding the dark side of the ostensible fancier successor of the Internet of today, thereby its value and contribution to the ongoing scholarly debates in the field of Science, Technology, and Society (STS). In addition, by shedding light on the emergence of the Metaverse as a computing platform, the viewpoint seeks to help policymakers understand and assess the ramifications of its wide adoption, as well as to help users make informed decisions about its usage in everyday activity—if it actualizes.